Gabapentin therapy for pruritus in haemodialysis patients: a randomized, placebo-controlled, double-blind trial - Gunal, AI; Ozalp, G; Yoldas, TK; Gunal, SY; Kirciman, E; Celiker, H (Oxford Univ Press, 2004)
Background. Uraemic pruritus is a common and distressing symptom in patients on haemodialysis for chronic renal failure. Gabapentin is an anticonvulsant that alleviates neuropathic pain. We conducted a double-blind. placebo-controlled, crossover study to assess its effectiveness against renal itch. Methods. We enrolled in the trial 25 adult patients on haemodialysis who were asked to daily record the severity of their pruritus on a visual analogue scale. The patients were randomly assigned to receive gabapentin for 4 weeks followed by placebo for 4 weeks or the reverse sequence. Gabapentin or placebo were administered thrice weekly, at the end of haemodialysis sessions. Results. The mean pruritus score of the cohort before the study was 8.4 +/- 0.94. After placebo intake, it decreased to 7.6 +/- 2.6 (P = 0.098). The score of four patients decreased by >50% following placebo. After gabapentin administration, the mean score decreased significantly, to 1.2 +/- 1.8 (P = 0.0001), although one patient's symptoms did not improve significantly. No patient dropped out of the study due to adverse effects from gabapentin. Conclusions. Our study shows that gabapentin is safe and effective for treating uraemic pruritus in haemodialysis patients. Our results also support the neuropathic hypothesis of uraemic pruritus.
Keywords: gabapentin; haemodialysis; uraemic pruritus